DETERMINATION OF MINERAL Ca CONTENT IN SEVERAL KINDS OF FRESH FOOD AND PROCESSED PRODUCTS AS SWEETMEAT - Ahmad Syukur Hasibuan; Fahma Shufyani; Rinaldo Rinaldo (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2019)
The basic thing that differentiate both is how to make it, lasting power, and design products. This study aims to determine the level of calcium in the sample of fresh guava, ginger, and nutmeg, and to investigate the mineral calcium levels in samples of fresh and processed products as wet sweetmeat and dry sweetmeat. Each sample must first be destructed by dry destruction, then the mineral assay performed with quantitative assay atomic absorption spectrophotometry (AAS) using a gas burner nitrous oxide-acetylene at a wavelength of 422.7 nm. The advantage of this method is to have a high sensitivity (limit of detection of less than 1 ppm), and the implementation is relatively simple. Calcium levels in samples of fresh guava, ginger and nutmeg in a row each each sample as follows (7.7105 ± 0.1224) mg / 100 g, (14.5232 ± 0.117) mg / 100 g and (38, 8834 ± 0.6996) mg / 100 g. In the wet sweetmeat guava, ginger and nutmeg for (13.7787 ± 0.4123) mg / 100 g, (22.8345 ± 0.8247) mg / 100 g and (0.2284 ± 0.3759) mg / 100 g. While on dry sweetmeat guava, ginger and nutmeg for (160.9401 ± 0.4223) mg / 100 g, (176.0465 ± 1.0458) mg / 100 g and (120.4426 ± 0.7932) mg / 100 g. Levels of calcium contained in a sample of fresh guava, ginger and nutmeg and sweetmeat processed as wet and dry sweetmeat has different levels